RELASI UMAT KHONGHUCU DENGAN MASYARAKAT SEKITAR DAN PEMERINTAH DIKAWASAN PECINAN - suhanah suhanah (Harmoni, 2018)
The objective of the study is to understand forms of harmony of religious society in the Pecianan region. This includes any services for Confucian society that have been or have not been provided by the government. This study is also aimed at analysing the relations of Confucian society with surrounding religious communities, as well as with the society and the government, which are able to create religious harmony. This research applies qualitative approach in the form of case study. The data collection is conducted through interview, observation, documentary study, and library inquiry. The research discovers that the harmony is well maintained in the Pecinan region. At least, the Confucian society are able to perform their rituals and worships very well. The government have provided several services such as birth certificate, identity card (KTP), and education. However, the government has not provided other services such as Higher Academy of Confucianism. The relations of Confucian society with surrounding religious communities is developed well, even though there have been some small frictions that fortunately did not come to the surface. Generally, there have been harmonisation between religious communities in Semarang City, especially in the Pecinan region that is the reservoir of Confucian society.